Hierarchical hetero-Ni3Se4@NiFe LDH micro/nanosheets as efficient bifunctional electrocatalysts with superior stability for overall water splitting. Issue 5 (24th April 2019) - Zhang, Tao; Hang, Lifeng; Sun, Yiqiang; Men, Dandan; Li, Xinyang; Wen, Lulu; Lyu, Xianjun; Li, Yue
Abstract : Hierarchical hetero-Ni3 Se4 @NiFe LDH micro/nanosheets were prepared by coupling NiFe LDH nanosheets with Ni3 Se4 micro-sized sheets, and could be used as bifunctional electrocatalysts with excellent activity and durability for overall water splitting. Abstract : Hierarchical hetero-Ni3 Se4 @NiFe LDH (layered double hydroxide) micro/nanosheets were prepared by coupling NiFe LDH nanosheets with Ni3 Se4 micro-sized sheets, and could be used as effective bifunctional electrocatalysts for water splitting. Benefiting from the strong electronic interaction between the NiFe LDH nanosheets and Ni3 Se4 micro-sized sheets, the hierarchical hetero-Ni3 Se4 @NiFe LDH micro/nanosheets are endowed with enhanced charge transfer and reaction kinetics. As a result, the obtained hierarchical hetero-Ni3 Se4 @NiFe LDH/CFC (carbon fiber cloth) electrode shows optimized hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) properties in alkaline medium with a small overpotential of 85 mV and 223 mV at the current density of 10 mA cm −2, respectively. When the hierarchical hetero-Ni3 Se4 @NiFe LDH/CFCs are used as bifunctional electrodes for overall water splitting in a two-electrode electrolyzer, the current density of 10 mA cm −2 is derived at a cell voltage of 1.54 V. Moreover, due to the stability of the novel hierarchical hetero-micro/nanostructure, the as-prepared Ni3 Se4 @NiFe LDH/CFC exhibited high stability in the electrochemical processes over 100 h. This work highlights the importance of constructing efficient bifunctional electrocatalysts for overall water splitting by rational design of heterostructures.